Features of the Main Processes of the Natural Population Movement in the Republic of Sakha – Yakutia - LEBEDEVA, Ulyana Mikhailovna; MINGAZOVA, Elmira Nurislamovna; LOZOVSKAYA, Svetlana Artemievna; STEPANKO, Nataliia Grigorievna; LATYSHEVA, Larisa Alekseevna (Journal of Environmental Management and Tourism; Vol 12 No 5 (2021): JEMT Volume XII Issue 5(53) Fall 2021DO - 10.14505/jemt.12.5(53).13, 2021)
The relevance of the stated research topic is determined by the need for a clear understanding of the population movement issues in the region of the country, in the context of existing social problems. The purpose of this scientific study is to examine in detail the data on the main trends and rates of the natural population movement using the example of the Republic of Sakha (Yakutia), with a separate analysis of the age-specific birth and mortality rates. The data on the main trends and indicators of the natural population movement on the example of the Republic of Sakha (Yakutia) are considered in detail in the article. The age-specific birthrates and deathrates are analyzed separately. The research methods included: the method of studying and generalization of experience, analytical, statistical, sociological methods. The results obtained indicate that in the Republic of Sakha (Yakutia) the high rates of natural population growth are observed in comparison with other subjects of the Russian Federation, there is also a low mortality rate, especially infant mortality. It was revealed that the main mortality factors in the republic are diseases of the circulatory system and neoplasms. The fact of the relationship between mortality rates from diseases of the circulatory system and mortality from diseases of the digestive system has been determined. The authors consider prospects for subsequent scientific research in this direction by obtaining the ability to predict the development of trends in population movement in individual geographic regions from the viewpoint of the negative factor influence on changes in the population of a geographic region.